2022
DOI: 10.52904/0718-4646.2022.578
|View full text |Cite
|
Sign up to set email alerts
|

El sector forestal y su evolución, la situación actual de los bosques nativos y costos de rehabilitación de bosques nativos degradados

Abstract: Se reseña el sector forestal chileno y la situación actual de sus bosques nativos. Se describe una experiencia de rehabilitación mediante plantación suplementaria, en la región de los Ríos, de bosques Siempreverde degradados por intervenciones extractivas del pasado y posterior invasión de quilantales. Se determina los costos de la intervención y se enfatiza la necesidad de emplear material genético adecuado para la misma, aspecto que es determinante para el éxito y para la capacidad de adaptación de la nueva … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…is an important forest species and native to Atlantic and Mediterranean regions of southern Europe and northern Africa. Currently, natural populations and productive reforestations of P. pinaster are distributed across 1.4 million of hectares in Spain (Bravo et al 2017), approximately 700 000 hectares in Portugal, as reported in 2015 (ICNF 2019) and over 1 million hectares in France ( IGN 2022). Although P. pinaster has diminished in recent years due to major wild res (Picos and Rodríguez-Soalleiro 2019) and the preference for Eucalyptus spp.…”
Section: Introductionmentioning
confidence: 99%
“…is an important forest species and native to Atlantic and Mediterranean regions of southern Europe and northern Africa. Currently, natural populations and productive reforestations of P. pinaster are distributed across 1.4 million of hectares in Spain (Bravo et al 2017), approximately 700 000 hectares in Portugal, as reported in 2015 (ICNF 2019) and over 1 million hectares in France ( IGN 2022). Although P. pinaster has diminished in recent years due to major wild res (Picos and Rodríguez-Soalleiro 2019) and the preference for Eucalyptus spp.…”
Section: Introductionmentioning
confidence: 99%